Irreducible polynomials of maximum weight - Ahmadi, Omran; Menezes, Alfred (Utilitas Mathematica, 2007)
We establish some necessary conditions for the existence of irreducible polynomials of degree n and weight n over n duble struck F sign2. Such polynomials can be used to efficiently implement multiplication in duble struck F sign2n. We also provide a simple proof of a result of Bluher concerning the reducibility of a certain family of polynomials.